Synthesis of acetaldehyde based on acetylene in liquid phase - N. S. Tangyarikov; Sh. Hazratkulov (Zien Journals, 2023)
New mixed polyfunctional catalysts for the hydration of acetylene to acetaldehyde and acetone have been developed, their properties have been developed, and various ways of formation of acetylene by the reaction of hydration condensation have been proposed
Keywords: acetic acid; acetic anhydride; ethyl alcohol; pentaerythritol